The Epidemiology of Fractures Caused by Falls Down Stairs. (17th June 2013) - Mitchell, Sarah E.; Aitken, Stuart A.; Court-Brown, Charles M.
Abstract : Fractures sustained from a fall down stairs have received little attention in the orthopaedic literature. We have undertaken a study of these fractures to determine their epidemiology and to compare it to that of fractures caused by a standing fall. All new patients presenting with a fracture between July 2007 and June 2008 were prospectively identified. Falls down stairs caused 261 fractures and were the fifth commonest mode of injury in all ages but the second commonest in those aged 65 years or over. Patients in this category were significantly younger than those with a fracture from a standing fall (54.6 yrs versus 64.9 yrs, P < 0.001 ). Fractures of the ankle (odds ratio (OR) 1.9, P < 0.001 ), talus (OR 3.0, P = 0.04 ), calcaneus (OR 9.7, P < 0.001 ), midfoot (OR 6.9, P < 0.001 ), toe phalanges (OR 12.0, P < 0.001 ), scapula (OR 4.6, P = 0.002 ), and proximal ulna (OR 2.4, P = 0.04 ) were significantly more likely to result from a fall involving stairs. When grouped together, the odds of any foot or ankle fracture resulting from a fall down stairs were approximately double when compared with a fall from standing (OR 2.1, P < 0.001 ). There was a trend towards increased fracture incidence from falls down stairs with worsening social deprivation (r = 0.63, P = 0.05 ). A fall down stairs poses a substantial risk of fractures of the foot, ankle, and scapula. When examining patients with this mechanism of injury, these fracture types should be excluded.